Исследование изменения морфологии нанопленок золота, нанесенных на оксидные материалы, при отжиге - Габ, И.И.; Костюк, Б.Д.; Стецюк, Т.В.; Куркова, Д.И.; Шевченко, А.В.; Дукаров, С.В.; Крышталь, А.П. (My University, 2009)
Changes of morphology gold nanofilms 200 nm thickness which sputtered onto oxide materials as a result annealing of them in vacuum at temperatures 800–1100°C are investigated. It is established that fragmentation films of given thickness is proceeds enough intensively at 900°C, and after heating of them up to 1000°C the films break up to separate drops and the further heating these films up to 1100°C essential changes in morphology of them are not observed. Distinction in morphology films which were annealed as in vacuum and as in air is revealed. In the latter case process of film disintegration occurs more slowly and at higher temperatures comparison with annealing in vacuum. . . . . . . . . . . . . . . . . . Исследованы изменения морфологии, которые происходят в золотых нанопленках толщиной 200 нм, нанесенных на оксидные материалы, в результате отжига их в вакууме при температурах 800–1100°С. Установлено, что при данной толщине фрагментация пленок протекает достаточно интенсивно при 900°С, а при нагреве до 1000°С пленка распадается на отдельные капли и дальнейший нагрев до 1100°С существенных изменений в морфологию пленки не вносит. Обнаружено различие в морфологии пленок, отожженных в вакууме и на воздухе. В последнем случае процесс распада пленки происходит медленнее и при более высоких температурах.
Research of gold nanofilms deposited onto oxide materials morphology changes during annealing
Keywords: Thin films; dispergation; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces